Laboratory Study of the Use of Additional Reacted and Activated Rubber (RAR) Materials on Asphalt Concrete-Wearing Course (AC-WC) Mix - Bayu Tirta Leksana Purnomo; Latif Budi Suparman; Agus Taufik Mulyono (International Journal of Multi Discipline Science, 2019)
The development of infrastructure in Indonesia was increasing. The government focuses on boosting infrastructure development to create long-term economic growth. Therefore, a qualified infrastructure was a standard of an advanced rapidly economy. One of them is under construction was road and toll road infrastructure. As a result of the development was the occurrence of the increasing volume of vehicles on the road. Due to this resulting in an increased load reposition and also increased vehicle load on the road, it was then combined with a wet tropical climate or humid warm areas in Indonesia that have high rainfall and temperatures that can reach 38oC, resulting in structural damage such as cracks, rutting, stripping, and pothole. Performance from pavement also declined faster than the estimated plan. Roads in Indonesia mostly use the type of concrete asphalt mixture. Characteristics for concrete asphalt prioritize stability. In fact, the most important thing was the stability and durability of the road. Various ways can be done to overcome the road damage and acquire the ideal characteristics such as the use of added materials to Hot Mix Asphalt. To improve the performance of pavement characteristics, the use of added materials was expected to overcome problems that are affected by temperature, weather, increased vehicle volume, and increased traffic load. The added materials are to enhance Reacted and Activated Rubber (RAR) which was a developed crumb rubber to increase durability and keep the level of road pavement stability.